Firm efficiency in Thailand’s telecommunication industry: Application of the stochastic frontier model with dependence in time and error components - Leurcharusmee S. (2017)
© Springer International Publishing Switzerland 2016. In this study, we measure the ability to produce and provide services of telecommunication firms in Thailand. We propose a methodology to estimate firm technical efficiency using the Stochastic Frontier Analysis (SFA) with copulas to capture both the dependence of the stochastic and inefficiency error components and the dependence of the errors across time. Allowing the dependence between the stochastic error and the aggregate error prevents the estimation of the technical efficiency from being biased. Moreover, allowing the time dependence for the aggregate error improves the efficiency of the model. The results show that the average technical efficiency is 0.54, which indicates a room for improvement in the industry.